2021
DOI: 10.1108/ecam-10-2020-0829
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of abusive supervision on employee' voice behavior in Chinese construction industry: a moderated mediation analysis

Abstract: PurposeThe purpose of this study is to explore the impact of abusive supervision on employees' voice in China's construction industry. Moreover, the authors explore the mediating role of ethics-related self-efficacy and work engagement and the moderating influence of psychological climate in explaining the association between abusive supervision and employee voice behavior.Design/methodology/approachThis study used data in pairs collected from 402 supervisors and employees of construction companies in Anhui, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 88 publications
1
24
0
Order By: Relevance
“…Our findings are based on a sample from China, and Chinese culture is built on collectivism (Li et al, 2014) rather than individualism, as it is in the West. Our findings backed with previous research that claimed organizational support is just as crucial in Eastern cultures as it is in Western cultures (Khan & Khan, 2021) and perhaps more important in Chinese culture due to collectivism. Thus, Chinese employees may be more accustomed to abusive supervision, and collectivist orientation helps to mitigate the harmful impacts of abusive supervision at work to some extent.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings are based on a sample from China, and Chinese culture is built on collectivism (Li et al, 2014) rather than individualism, as it is in the West. Our findings backed with previous research that claimed organizational support is just as crucial in Eastern cultures as it is in Western cultures (Khan & Khan, 2021) and perhaps more important in Chinese culture due to collectivism. Thus, Chinese employees may be more accustomed to abusive supervision, and collectivist orientation helps to mitigate the harmful impacts of abusive supervision at work to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…A recent past study has indicated that abusive supervision is a significant influencer of creativity (Khan et al, 2020). Another study found that abusive behaviour had an impact on workplace engagement (Khan & Khan, 2021). Furthermore, the mediating effect of job engagement was explored and found to be significant in the relationship between psychopathic behaviour and creativity in the Chinese tourism business (Khan et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed the conceptual model by using the SEM approach, and in prior studies, this approach [SEM: using Analysis of Moment Structures (AMOS) 24.0] has been extensively used ( Khan and Khan, 2021 ). Fit indices showed that the proposed model has an adequate fit (χ2/df = 273.619/184 = 1.487; CFI = 0.981; TLI = 0.987; and RMSEA = 0.031).…”
Section: Resultsmentioning
confidence: 99%